2006
DOI: 10.1103/physrevlett.96.173904
|View full text |Cite
|
Sign up to set email alerts
|

Antenna Model for Wire Lasers

Abstract: An antenna model is proposed for long (L ) lasers with subwavelength cross sections (wire lasers). It is shown that the far-field pattern of the wire lasers is determined by the ratio of the wavelength to the length. The radiation of the wire laser is predicted to be concentrated in a narrow beam ' 2=L p for laser modes where the longitudinal phase velocity is in synchronism with the velocity of light in air. Experimental results obtained using a terahertz quantum cascade wire laser are in agreement with the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
45
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 19 publications
3
45
0
Order By: Relevance
“…These values, which are similar to those calculated in Ref. 13, agree quite well with the experimental data, and account for the essential interference phenomena observed. It can also be understood that for the beam patterns presented in Fig.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…These values, which are similar to those calculated in Ref. 13, agree quite well with the experimental data, and account for the essential interference phenomena observed. It can also be understood that for the beam patterns presented in Fig.…”
supporting
confidence: 81%
“…Description of the details of this model, however, is outside the scope of this letter and will be presented elsewhere. 13 To obtain some insight into the physical origin of these interference patterns, we use an extremely simplified version of this model. We describe the emission of the laser bar with length L as resulting from a system of two coherent point sources situated at the two laser end facets, radiating into free space at a wave- length .…”
mentioning
confidence: 99%
“…4(a). Strong modulations of far-field intensity are almost axially symmetrical, with the separation of intensity rings in agreement with the wire laser model [6]. Radiation of the laser was partially blocked by the sample holder, leading to a smaller intensity in the lower part of Fig.…”
Section: Image Beam From a Wire Laser Physical Review A 91 051802(r)supporting
confidence: 61%
“…It was found to be highly divergent, with strong intensity modulations observed both in far [4] and near field [5], with the pattern of modulations more dense for longer lasers. It was shown that the far-field pattern of wire lasers is formed by the interference of radiation from the longitudinal distribution of sources along the laser waveguide [6] and is similar to that of antennas of traveling wave. Thus it depends strongly on the longitudinal phase velocity of the waveguide mode.…”
mentioning
confidence: 99%
See 1 more Smart Citation